Kalir Was A Tanna: Rabbenu Tam's Invocation of Antiquity in Defense of the Ashkenazi Payyetanic Tradition - Langer, Ruth (Hebrew Union College annual, 1996)
One of the central arenas of controversy in the medieval world between actual synagogue custom and the Babylonian talmudic traditions was the question of the legitimacy of the insertion of liturgical poetry (piyyut) into the statutory prayers. A variety of arguments against piyyut by influential sages eventually led to the elimination or marginalization of this poetry in most Sephardi rites. In Ashkenaz, in contrast, the tradition continued into the modern period, largely because of the great importance placed there on maintaining ancestral custom, but also because of the vigorous defense of this custom by several sages, the most important of which was Rabbenu Tam. In this paper, I analyze Rabbenu Tam's famous responsum defending piyyut and suggest that his unprecedented identification of Kalir as the second-century Tanna, Rabbi Elazar beRabbi Shimon, is a) a deliberate invocation of the authority placed on antiquity in Judaism, especially in Ashkenaz; and b) likely a specific response to the challenges to Kalirian piyyut raised by Abraham Ibn Ezra and other Spanish emigres.